A comparison study of face stability between the entering and exiting a shallow-buried tunnel with a front slope - Li, Xinzhe; Li, Xiulei; Yang, Chao (Frontiers in Earth Science, 2022)
Worldwide, it is a great challenge to tunnel in portal section, where excessive deformation, cracking, or even collapse often occurs during the construction process. This paper presents a comparison study of face stability between entering and exiting a shallow-buried tunnel with a front slope. Firstly, the theoretical solutions of support pressure σT and safety coefficient FS of the excavation face considering surface slope are derived by upper-bound limit analysis method. Secondly, for different slope angles, buried depth and surrounding rocks of the exit and entrance sections, the σT and FS are obtained. The results show that when the burial depth of the tunnel crown h remain constant, the σT increased first and then decreased while the FS increased gradually, and both become steady when the slope angle α arrive at a certain value. In addition, the thicker the h is, the smaller the certain value α is. When the h and α remain constant, the loose area in front of the excavate face will decreased apparently with the increase of the internal friction angle φ, thus the σT will decrease and FS will increase. Moreover, the σT decreased linearly with the increase of cohesion c and unit weigh γ of surrounding rock, while the FS is the opposite. Compared with the entrance section, the construction risk at the exit section is greater.